Collaborative Software Modeling in Virtual Reality - Yigitbas, Enes; Gorissen, Simon; Weidmann, Nils; Engels, Gregor (Software Engineering 2022, Fachtagung des GI-Fachbereichs Softwaretechnik, 21.-25. Februar 2022, Virtuell)

Search Space Characterization for Approximate Logic Synthesis - Witschen, Linus Matthias; Wiersema, Tobias; Reuter, Lucas David; Platzner, Marco (2022 59th ACM/IEEE Design Automation Conference (DAC))

MUSCAT: MUS-based Circuit Approximation Technique - Witschen, Linus Matthias; Wiersema, Tobias; Artmann, Matthias; Platzner, Marco (Design, Automation and Test in Europe (DATE))

High-Bandwidth Arbitrary Signal Detection Using Low-Speed Electronics - Meier, Janosch; Singh, Karanveer; Misra, Arijit; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (IEEE Photonics Journal)
The growing demand for bandwidth and energy efficiency requires new solutions for signal detection and processing. We demonstrate a concept for high-bandwidth signal detection with low-speed photodetectors and electronics. The method is based on the parallel optical sampling of a high-bandwidth signal with sinc-pulse sequences provided by a Mach-Zehnder modulator. For the electronic detection and processing this parallel sampling enables to divide the high-bandwidth optical signal with the bandwidth B into N electrical signals with the baseband bandwidth of B/(2N) . In proof-of-concept experiments with N=3 , we present the detection of 24 GHz optical signals by detectors with a bandwidth of only 4 GHz. For ideal components, the sampling and bandwidth down-conversion does not add an excess error to the signals and even for the non-ideal components of our proof-of-concept setup, it is below 1%. Thus, the rms error for the measurement of the 24 GHz signal was reduced by a factor of about 3.4 and the effective number of bits were increased by 1.8.

Locking of microwave oscillators on the interharmonics of mode-locked laser signals - Bahmanian, Meysam; Kress, Christian; Scheytt, Christoph (Optics Express)
In this paper, the theory of phase-locking of a microwave oscillator on the interharmonics, i.e. non-integer harmonics, of the repetition rate of the optical pulse train of a mode-locked laser (MLL) is developed. A balanced optical microwave phase detector (BOMPD) is implemented using a balanced Mach-Zehnder modulator and is employed to discriminate the phase difference between the envelope of the optical pulses and the microwave oscillator. It is shown mathematically that the inherent nonlinear properties of BOMPD with respect to the microwave excitation amplitude can be used for interharmonic locking. The characteristic functions of the phase detector for interharmonic locking are derived analytically and are compared with the measurement results. An opto-electronic phase-locked loop (OEPLL) is demonstrated whose output frequency locks on interharmonics of the MLL repetition rate when an appropriate modulator bias and sufficient RF amplitude are applied. Thus, for the first time theory and experiment of reliable locking on interharmonics of the repetition rate of a MLL are presented.

Evaluation of Algorithms for the Node Capacitated Clique - Roopa, Rajanna

Aufarbeitung und lmplementierung von DAG-Rider - Korzeczek, Sebastian

Hybrid Routing in Three Dimensions - Nachtigall, Marcel

mobile-env: An Open Platform for Reinforcement Learning in Wireless Mobile Networks - Schneider, Stefan Balthasar; Werner, Stefan; Khalili, Ramin; Hecker, Artur; Karl, Holger (IEEE/IFIP Network Operations and Management Symposium (NOMS))
Recent reinforcement learning approaches for continuous control in wireless mobile networks have shown impressive results. But due to the lack of open and compatible simulators, authors typically create their own simulation environments for training and evaluation. This is cumbersome and time-consuming for authors and limits reproducibility and comparability, ultimately impeding progress in the field. To this end, we propose mobile-env, a simple and open platform for training, evaluating, and comparing reinforcement learning and conventional approaches for continuous control in mobile wireless networks. mobile-env is lightweight and implements the common OpenAI Gym interface and additional wrappers, which allows connecting virtually any single-agent or multi-agent reinforcement learning framework to the environment. While mobile-env provides sensible default values and can be used out of the box, it also has many configuration options and is easy to extend. We therefore believe mobile-env to be a valuable platform for driving meaningful progress in autonomous coordination of wireless mobile networks.
Keywords: wireless mobile networks; network management; continuous control; cognitive networks; autonomous coordination; reinforcement learning; gym environment; simulation; open source

ROM-Based Multiobjective Optimization of Elliptic PDEs via Numerical Continuation - Banholzer, Stefan; Gebken, Bennet; Dellnitz, Michael; Peitz, Sebastian; Volkwein, Stefan (Non-Smooth and Complementarity-Based Distributed Parameter Systems)
Multiobjective optimization plays an increasingly important role in modern applications, where several objectives are often of equal importance. The task in multiobjective optimization and multiobjective optimal control is therefore to compute the set of optimal compromises (the Pareto set) between the conflicting objectives. Since the Pareto set generally consists of an infinite number of solutions, the computational effort can quickly become challenging which is particularly problematic when the objectives are costly to evaluate as is the case for models governed by partial differential equations (PDEs). To decrease the numerical effort to an affordable amount, surrogate models can be used to replace the expensive PDE evaluations. Existing multiobjective optimization methods using model reduction are limited either to low parameter dimensions or to few (ideally two) objectives. In this article, we present a combination of the reduced basis model reduction method with a continuation approach using inexact gradients. The resulting approach can handle an arbitrary number of objectives while yielding a significant reduction in computing time.

Efficient Virtual Design and Testing of Autonomous Vehicles - Peitz, Sebastian; Dellnitz, Michael; Bannenberg, Sebastian (German Success Stories in Industrial Mathematics)
With the ever increasing capabilities of sensors and controllers, autonomous driving is quickly becoming a reality. This disruptive change in the automotive industry poses major challenges for manufacturers as well as suppliers as entirely new design and testing strategies have to be developed to remain competitive. Most importantly, the complexity of autonomously driving vehicles in a complex, uncertain, and safety-critical environment requires new testing procedures to cover the almost infinite range of potential scenarios.

Compensation of LF Common-Mode Noise by the internal DC/DC-Stage for transformerless On-Board Chargers at Three- and Single-Phase Operation - Schafmeister, Frank (International Conference on Electric & Electronic in Hybrid and Electric Vehicles and Electric Energy Management (EEHE),)

An Open-Source Transistor Database and Toolbox as an Unified Software Engineering Tool for Managing and Evaluating Power Transistors - Förster, Nikolas; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (Proc. 37th IEEE Applied Power Electronics Conference (APEC))

Robust Hysteresis Control for LLC Resonant Converters Using a Fully Isolated Measurement Scheme - Keuck, Lukas; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Resonant evanescent excitation of OAM modes in a high-contrast circular step-index fiber - Hammer, Manfred; Ebers, Lena; Förstner, Jens (Complex Light and Optical Forces XVI)
Resonant evanescent coupling can be utilized to selectively excite orbital angular momentum (OAM) modes of high angular order supported by a thin circular dielectric rod. Our 2.5-D hybrid-analytical coupled mode model combines the vectorial fields associated with the fundamental TE- and TM-modes of a standard silicon photonics slab waveguide, propagating at oblique angles with respect to the rod axis, and the hybrid modes supported by the rod. One observes an efficient resonant interaction in cases where the common axial wavenumber of the waves in the slab matches the propagation constant of one or more modes of the rod. For certain modes of high angular order, the incident wave is able to transfer its directionality to the field in the fiber, exciting effectively only one of a pair of degenerate OAM modes
Keywords: tet_topic_waveguide

Continuous and discrete Noether's fractional conserved quantities for restricted calculus of variations - Cresson, Jacky; Jiménez, Fernando; Ober-Blöbaum, Sina (AIMS)

Semi-guided waves in integrated optical waveguide structures - Ebers, Lena
In dieser Arbeit wird die elektromagnetische Wellenausbreitung in integrierten optischen Wellenleitern mit Hilfe von halb analytischen und numerischen Simulationsmethoden untersucht. Im ersten Teil werden 2-D Si/SiO2-Wellenleiterkonfigurationen mit hohem Brechungsindexkontrast betrachtet. Die Strukturen werden mit halb geführten Wellen unter schrägen Ausbreitungswinkeln angeregt. Dadurch kann die Leistungsübertragung zu bestimmten ausgehenden Moden unterdrückt werden, wodurch vollständig verlustfreie Systeme entstehen. Zusätzlich dient die Anregung mit einem seitlich begrenzten, einfallenden Wellenbündel aus halb geführten Wellen dazu, praktisch relevantere 3-D Konfigurationen zu realisieren. Darüber hinaus wird eine schrittweise Winkelspektrum-Methode vorgestellt, die es ermöglicht, in Kombination mit voll vektoriellen 2-D Finite-Elemente-Lösungen für Teilprobleme mit geringerer Komplexität, die Wellenausbreitung in planaren, linsenförmigen Wellenleitern numerisch in drei Raumrichtungen zu berechnen. Im zweiten Teil dieser Arbeit wird die Ausbreitung in Wellenleiterstrukturen aus Lithiumniobat untersucht, welche für quantenoptische Effekte genutzt werden. Zur Detektion einzelner Photonen werden supraleitende Nanodrähte auf eindiffundierten Lithiumniobat Wellenleitern mit zusätzlicher Taperschicht aus Silizium betrachtet. Um die Wellenausbreitung in diesen 3-D Wellenleitern zu beschreiben, wird eine einseitig gerichtete Finite-Elemente „Modal Matching“ Methode eingeführt. Abschließend werden Rippenwellenleiter aus Lithiumniobat analysiert, die auf Siliziumdioxid Plattformen aufgebracht sind. Der Schwerpunkt liegt hier auf dem nichtlinearen „Parametric Down-Conversion“ Prozess, der für die Erzeugung verschränkter Photonen verwendet wird.
Keywords: tet_topic_waveguide

Work-in-Progress: The Potential of Interactive Scripts – Supporting Conceptual Understanding and Collaborative Problem-Solving Skills - Temmen, Katrin; Kersten, Peter; Schäfer, Dominik (Mobility for Smart Cities and Regional Development - Challenges for Higher Education)

Comparative Evaluation of MVAC-LVDC SST and Hybrid Transformer Concepts for Future Datacenters - Huber, Jonas; Wallmeier, Peter; Pieper, Ralf; Schafmeister, Frank; Kolar, Johann (Proc. 9th IEEJ International Power Electronics Conference (IPEC))

Turnpike Property in Optimal Microbial Metabolite Production - Caillau, Jean-Baptiste; Djema, Walid; Gouzé, Jean-Luc; Maslovskaya, Sofya; Pomet, Jean-Baptiste (Journal of Optimization Theory and Applications)
Abstract We consider the problem of maximization of metabolite production in bacterial cells formulated as a dynamical optimal control problem (DOCP). According to Pontryagin’s maximum principle, optimal solutions are concatenations of singular and bang arcs and exhibit the chattering or Fuller phenomenon, which is problematic for applications. To avoid chattering, we introduce a reduced model which is still biologically relevant and retains the important structural features of the original problem. Using a combination of analytical and numerical methods, we show that the singular arc is dominant in the studied DOCPs and exhibits the turnpike property. This property is further used in order to design simple and realistic suboptimal control strategies.
Keywords: Applied Mathematics; Management Science and Operations Research; Control and Optimization